2023
DOI: 10.1088/2051-672x/acb9a9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of current density on tribological properties of micro-arc oxidation ceramic film on Al-Mg-Sc alloy

Abstract: Ceramic films on Al-Mg-Sc alloy were prepared in alkaline sodium silicate electrolyte solution at different current densities by micro-arc oxidation (MAO) technique. The influence of current density on the microstructure and tribological property of the MAO ceramic films was investigated. The experimental results indicated that the surface porosity decreased and roughness increased with the increase of current density. The optimal anti-friction effect of the MAO ceramic film prepared at the current density of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…The figure demonstrates that the sample contains mainly C–O/CO and Al–O forms of O, where Al–O is derived from Al–O. Additionally, Figure d exhibits the high-resolution XPS spectrum of Al 2p, indicating that Al primarily exists in the form of Al–O …”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The figure demonstrates that the sample contains mainly C–O/CO and Al–O forms of O, where Al–O is derived from Al–O. Additionally, Figure d exhibits the high-resolution XPS spectrum of Al 2p, indicating that Al primarily exists in the form of Al–O …”
Section: Resultsmentioning
confidence: 91%
“…To improve the tribological performance of MAO coatings, various related studies have been conducted by researchers. Currently, research on MAO coatings mainly focuses on three aspects: adjusting power supply parameters, optimizing electrolyte composition, and developing composite coatings. ,, The first focus is on the influence of power supply parameters and electrolyte composition on coating performance. Li et al investigated the effect of cathode voltage on the performance of MAO coatings, and a suitable negative voltage could produce denser MAO coatings with superior tribological properties .…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al showed that for Al-Mg-Sc alloys, the effect of increasing current density is such that it decreases the resulting PEO coating porosity and increases the roughness. The wear properties were found to be optimal for higher current densities (10 A/dm 2 ), which was attributed to the higher thickness and good adhesion of the oxide film to the substrate [27]. A similar study was also conducted for AZ31 alloy [17], where pore sizes were larger at higher current densities, while their number decreased, and the same current density was found to be optimal.…”
Section: Introductionmentioning
confidence: 71%